The prospective association between periodontal disease and brain imaging outcomes: The Atherosclerosis Risk in Communities study. (27th January 2022) - Adam, Hamdi S.; Lakshminarayan, Kamakshi; Wang, Wendy; Norby, Faye L.; Mosley, Thomas; Walker, Keenan A.; Gottesman, Rebecca F.; Meyer, Katie; Hughes, Timothy M.; Pankow, James S.; Wong, Dean F.; Jack, Clifford R.; et al.
Abstract: Aim: We investigate if periodontal disease is prospectively associated with cerebrovascular and neurodegenerative markers of dementia and Alzheimer's pathology. Materials and Methods: N = 1306 participants (Visit 5 mean age = 76.5 [standard deviation = 5.4] years) in the Atherosclerosis Risk in Communities study with completed dental exams at Visit 4 underwent brain magnetic resonance imaging scans at Visit 5 while N = 248 underwent positron emission tomography scans. Participants were classified as edentulous or, among the dentate, by the modified Periodontal Profile Class. Brain volumes were regressed on periodontal status in linear regressions. Cerebrovascular measures and β‐amyloid positivity were regressed on periodontal status in logistic regressions. Results: Periodontal disease was not associated with brain volumes, microhaemorrhages, or elevated β‐amyloid. Compared with periodontally healthy individuals, odds ratios [95% confidence interval] for all‐type infarcts were 0.37 [0.20, 0.65] for severe tooth loss and 0.56 [0.31, 0.99] for edentulous participants. Conclusions: Within the limitations of this study, periodontal disease was not associated with altered brain volumes, microhaemorrhages, or β‐amyloid positivity. Tooth loss was associated with lower odds of cerebral infarcts.